PENGARUH PENGETAHUAN, PERSEPSI, PARTISIPASI MASYARAKAT DAN PERAN SERTA PEMERINTAH TERHADAP KONDISI LINGKUNGAN PERAIRAN SUNGAI SAIL KOTA PEKANBARU - Abdul Kodir Jailani; Thamrin Thamrin; Firdaus Firdaus (Program Pascasarjana Universitas Riau, 2014)
Research on the influence of knowledge, perception, participation society and role ofgovernment to environment condition of Sail River City of Pekanbaru has been held forthree months (January to March 2013) using survey methods to Sail river society withdirect interview use kuisioner to 100 responden which Linkert scale. Sampling locationdetermined by purposive in three location considering density and contiguity of Sailriver society. Research variable is knowledge, perception, participation society and roleof government to environment condition of Sail river with data analysis : descriptiveanalysis, rank Spearman'S correlation analysis, linear regresi analysis and hypothesisanalysis using F test. Research result of indicate the condition of Sail river haveminimal condition (score 1,98). There are influence which individually correlation withpositive direction of society participation variable (R 2 = 0,839) and government role(R 2 = 0,861) to condition of Sail river. While by simultan, variable knowledge (X 1 ),perception (X 2 ), participation (X 3 ) and role of government (X 4 ) influence the Conditionof Sail river (Y) equal to 78,2% (R 2 = 0,782) with F value > F table (89,967 > 2,47)meaning that knowledge, perception, participation society and governmental role havean effect on to condition of environment condition of Sail River.